Prevalence, Predictors, and Characteristics of Waterpipe Smoking Among Jazan University Students in Saudi Arabia: A Cross-Sectional Study - Salih, Sarah (Ann Glob Health, 2020)
BACKGROUND: Waterpipe smoking (WPS), also called shisha, has considerable short and long-term effects on human health. WPS has become increasingly popular among the youth in Jazan society. Hence, this study is aimed to assess the prevalence, predictors, and characteristics (knowledge and attitude) of WPS among male and female students at Jazan University. METHODS AND MATERIALS: A descriptive, cross-sectional study was conducted among 405 students. Data were collected using a self-administered validated questionnaire. The prevalence and predictors of WPS and the association between important socio-demographic factors (sex, type of college, parents smoking, home mate smoking and close friend smoking) were studied. RESULTS: The prevalence of WPS among students was high, approximately 34.0%. The prevalence rate was significantly higher in males (42.5%, n = 74) than in females (27.0%, n = 57) (p = 0.001). The main predictors of WPS were: being male (OR = 1.99, 95% CI [1.30, 3.06], p = 0.001), believing that shisha smoking is less harmful & addictive than cigarettes (OR = 3.84, 95% CI [1.88, 7.83], p < 0.001 and 3.80, 95% CI [2.0, 7.11], p < 0.001, respectively), and having a close friend who smokes (OR = 6.85, 95% CI [3.84, 12.22], p < 0.001). CONCLUSIONS: WPS prevalence among Jazan University students was high, and the most influential factors were being male, having smoker housemates and friends, and having incorrect thoughts and beliefs.